2018
DOI: 10.1155/2018/4271638
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of OqxAB Efflux Pump in Selection of Fluoroquinolone-Resistant Klebsiella pneumoniae

Abstract: The role of OqxAB efflux pump in Klebsiella pneumoniae was investigated in correlation with ciprofloxacin exposure. K. pneumoniae SE23 and K. pneumoniae SE191 were isolated from urinary tract infections and were analyzed in this study. Each carried oqxAB resistance determinant and exhibited ciprofloxacin MIC of 0.06 and 0.5 mg/L, respectively. Tested strains were initially exposed to their ciprofloxacin MIC values for 24 hours. Later on, the ciprofloxacin exposition has been increased to a daily 1, 2, 4, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…OqxAB, firstly identified on olaquindox resistance plasmids (pOLA52) in Escherichia coli of veterinary origin, is now widely distributed in diverse clinical MDR-KP genomes from humans [24]. Here, OqxAB pumps were presented in almost all isolates regardless of ciprofloxacin susceptibility, the bla-sequences of which varied, correlating with specific STs as a consequence of the transmission and evolution of the original sequence (oqxA1B1; pOLA52) from isolates of ST11, a finding that was consistent with the observation that ciprofloxacin concentration-dependent upregulation of OqxAB efflux pump in K. pneumoniae is clonally related [43]. Mobile quinolone pump, QepA, has not been detected in any hospital in PR China at present [13,33].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…OqxAB, firstly identified on olaquindox resistance plasmids (pOLA52) in Escherichia coli of veterinary origin, is now widely distributed in diverse clinical MDR-KP genomes from humans [24]. Here, OqxAB pumps were presented in almost all isolates regardless of ciprofloxacin susceptibility, the bla-sequences of which varied, correlating with specific STs as a consequence of the transmission and evolution of the original sequence (oqxA1B1; pOLA52) from isolates of ST11, a finding that was consistent with the observation that ciprofloxacin concentration-dependent upregulation of OqxAB efflux pump in K. pneumoniae is clonally related [43]. Mobile quinolone pump, QepA, has not been detected in any hospital in PR China at present [13,33].…”
Section: Discussionsupporting
confidence: 85%
“…pneumoniae [3, 46, 47]. AcrAB and OqxAB, two resistance–nodulation–division family pumps, made differential contributions to MDR and virulence [43, 48, 49]. In the absence of AcrAB, gyrase mutations fail to produce clinically relevant levels of resistance [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of genes oqxA and oqxB might also have contributed to the fluoroquinolone resistance profile of 26 K. pneumoniae. The plasmidic efflux pump OqxAB confers resistance to multiple agents, including fluoroquinolones as well as biocides, and has been shown to play a role in the selection of fluoroquinolone resistance in different K. pneumoniae clones [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it could be asserted that active efflux pump played a role in the observed level of antibiotic resistance. Szabo et al [22] and Maurya et al [23] reported the role of efflux pump in quinolone and β-lactam antibiotic resistance in Klebsiella pneumoniae strains isolated from clinical samples in Hungary and India respectively. Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%